Systemic Lupus Erythematosus Associated with Erythema Multiforme-Like Lesions - Ralph Yachoui; Patrick M. Cronin (Case Reports in Rheumatology)
Erythema multiforme (EM) and systemic lupus erythematosus (SLE) are common diseases. Their coexistence is known as Rowell syndrome (RS), first described in 1963. Only few cases of RS have been described and some of them questioned its existence. We present two cases of SLE in the setting of a newly developed EM-like eruption, which shares many similarities with the so-called Rowell syndrome.